Electrochemical Fine-Tuning of the Chemoresponsiveness of Langmuir-Blodgett Graphene Oxide Films - Devida, Juan Marcelo (2023)
Graphene oxide has been widely deployed in electrical sensors for monitoring physical, chemical, and biological processes. The presence of abundant oxygen functional groups makes it an ideal substrate for integrating biological functional units to assemblies. However, the introduction of this type of defects on the surface of graphene has a deleterious effect on its electrical properties. Therefore, adjusting the surface chemistry of graphene oxide is of utmost relevance for addressing the immobilization of biomolecules, while preserving its electrochemical integrity. Herein, we describe the direct immobilization of glucose oxidase onto graphene oxide-based electrodes prepared by Langmuir-Blodgett assembly. Electrochemical reduction of graphene oxide allowed to control its surface chemistry and, by this, regulate the nature and density of binding sites for the enzyme and the overall responsiveness of the Langmuir-Blodgett biofilm. X-ray photoelectron spectroscopy, surface plasmon resonance, and electrochemical measurements were used to characterize the compositional and functional features of these biointerfaces. Covalent binding between amine groups on glucose oxidase and epoxy and carbonyl groups on the surface of graphene oxide was successfully used to build up stable and active enzymatic assemblies. This approach constitutes a simple, quick, and efficient route to locally address functional proteins at interfaces without the need for additives or complex modifiers to direct the adsorption process.